The EFFECT OF THE INTERNAL CONTROL SYSTEM ON QUALITY OF THE BAZNAS FINANCIAL STATEMENTS, BANTEN PROVINCE WITH AMIL'S COMPETENCY AS INTERVENING VARIABLES - Erlina Sari Pohan (Program Studi Akuntansi Fakultas Ekonomi Universitas Sarjanawiyata Tamansiswa, 2021)
This study aims to of this thesis to find out whether there is an influence of the Internal Control System on the Quality of Financial Reports in BAZNAS Banten with Amil Competence as an Intervening Variable. Potential of zakat in Banten as measured by people who meet the nishob of zakat is Rp. 10 Trillion, however, from this potential, just realized Rp. 50 billion in Banten, this is assumed in the credibility of muzakki especially in the BAZNAS Banten which is still low due to fears that the donation given does not reach to those entitled to receive it (mustahik). The delay in reporting the use of zakat, infaq, and alms funds by the Zakat Collecting Unit (UPZ) in Banten also indicates that the internal control system between divisions at BAZNAS Banten is not well organized. The research method used in this thesis is a survey method and this is an associative thesis that discusses three variables are the independent variable, the dependent variable and the intervening variable. The results of this thesis can be concluded that the internal control system affects the quality of financial reports with amil competence as an intervening variable.